Examining the Impact of American Military Aid on the Russo-Ukrainian War - تومي وجدان; لخوص مريم (University of Eloued جامعة الوادي, 2025)
تمثل الحرب الروسية الأوكرانية، التي تصاعدت إلى غزو روسي كامل في فبراير 2022 بعد ضم القرم في 2014، دراسة حالة محورية في الحرب الحديثة والتنافس بين القوى العظمى. تبحث هذه الدراسة في تأثير المساعدات العسكرية الأمريكية على الصراع، معالجةً فجوة رئيسية في فهم كيف يشكل الدعم الخارجي الديناميكيات الاستراتيجية والتشغيلية للحروب غير المتكافئة. يتمحور الإشكال البحثي حول تقييم ما إذا كان الدعم الأمريكي قد عزز دفاعات أوكرانيا بشكل حاسم أم أدى إلى إطالة أمد الصراع دون حل واضح - وهو سؤال له تداعيات على سياسات المساعدات العسكرية المستقبلية وإدارة الصراعات. باعتماد منهجية نوعية تحليلية، تستخدم الدراسة تحليل الوثائق كإطار رئيسي. من خلال التحليل الموضوعي، تحدد الثيمات الاستراتيجية المتكررة في سياسات الدفاع الأمريكية (مثل الردع وإدارة التصعيد)، بينما يحلل المضمون لغة وأولويات التقارير الحكومية وتخصيصات المساعدات الكونغرسية. كما تدرس حالات معارك محورية (مثل هجوم خاركيف المضاد ودفاع باخموت) لربط توفير الأسلحة بالنتائج التكتيكية. تكشف النتائج أن المساعدات العسكرية الأمريكية (خاصة المدفعية المتطورة وأنظمة الدفاع الجوي والاستخبارات الفورية) عززت بشكل كبير قدرة أوكرانيا على استغلال نقاط الضعف اللوجستية الروسية، مما أعاق المكاسب التشغيلية لموسكو. لكن البحث يسلط الضوء أيضاً على تحديات منهجية: تزايد اعتماد أوكرانيا على الإمدادات الغربية، وتقلب الالتزامات السياسية الأمريكية، وغياب مسار واضح للنصر. دبلوماسياً، رفع الصراع مكانة أوكرانيا العالمية بينما اختبر تماسك التحالف بقيادة الولايات المتحدة. The Russo-Ukrainian war, which escalated into a full-scale Russian invasion in February 2022 following the 2014 annexation of Crimea, represents a critical case study in modern warfare and great-power competition. This study investigates the impact of United States military assistance on the conflict, addressing a key gap in understanding how external aid shapes the strategic and operational dynamics of asymmetric wars. The research problem centres on evaluating whether American support has decisively bolstered Ukraine's defence or inadvertently prolonged the conflict without a clear resolution, a question with significant implications for future military aid policies and conflict management. Adopting a qualitative, analytical methodology, the study employs documentary analysis as its primary framework. Through thematic analysis, it identifies recurring strategic themes in United States defence policies, such as deterrence and escalation management, while content analysis deciphers the language and priorities in government reports and congressional aid allocations. Case studies of pivotal battles, including the Kharkiv counteroffensive and Bakhmut defence, are examined to correlate weaponry provision with tactical outcomes. Findings reveal that United States military aid, particularly advanced artillery, air defence systems, and real-time intelligence, significantly enhanced Ukraine's capacity to exploit Russian logistical weaknesses, stalling Moscow's operational gains. However, the research also highlights systemic challenges: Ukraine's growing dependency on Western supplies, fluctuating United States political commitments, and the absence of a clear pathway to victory. Diplomatically, the conflict has elevated Ukraine's global stature while testing the limits of United States-led coalition cohesion.
Master's Degree In Literature and Civilization.2025
Keywords: المساعدات الأمريكية، الصراع الروسي الأوكراني، التأثير الاستراتيجي، أوكرانيا، الدعم العسكري الأمريكي; American aid; Russo-Ukrainian war; strategic impact; Ukraine; US military assistance